Impact of protein and carnitine consuption on outcomes of care development of full-term newborns with critical perinatal diseases - Anikin, I. O.; Varynskyi, V. O.; Stryzhak, L. S.; Serhieieva, L. N.; Snisar, V. I.; Анікін, Іван Олександрович; Варинський, Борис Олександрович; Стрижак, Лілія Сергіївна; Сергєєва, Л. Н.; Снісар, В. І. (My University, 2024)
There were studied results of the impact of increased consumption of proteins and L-carnitine in the nutrition program of full-term newborns with perinatal diseases on the results of physical development and inpatient treatment features. The purpose of the work was to study the correlations between short-term higher consumption of protein and carnitine by full-term newborns and the results of their physical development, the duration of hospital care development. The vital signs of 59 full-term newborns were studied in a randomized controlled trial in the period 2017-2020. The main critical disease of the perinatal period in newborns of both groups was found to be hypoxic-ischemic encephalopathy of a moderate degree in 86.7% and 86.2%, without a statistically significant difference. One group (n=30) received nutrition with mother's milk or formula, the second group (n=29) received similar nutrition with fortification with a protein and L-carnitine supplement during the hospital stay. At the beginning and at the end of the treatment, physical development of the newborns was studied and correlations between the obtained data were investigated. Newborns of both groups did not differ in characteristics at the beginning of the study. The proportions of the newborns' weight corresponded to the limits of the 50% percentile. The group with increased consumption of protein and carnitine, fortification group (FG) demonstrated better indicators of physical development, they regained body mass faster. Body mass of the newborns of the fortification group goup was 3966.9±439.1 g, compared to the standard nutrition (SN) group, with indicators being 3554.6±452.3 g, at p=0.003. The rate of increase in body length in FG was twice that of the SN group. Consumption of a larger dose of protein was accompanied by a shorter stay in the intensive care unit – 10.0 (8.0; 12.0) days versus 12.0 (11.0; 16.0) days, with U=235.0; p=0.002; earlier discharge from the hospital – 21.0 (19.0; 27.0) days versus 26.5 (22.0; 31.0) days, with U=267.0, p=0.01. Carnitine supplementation in the FG group led to an increase in the level of free carnitine in the blood plasma samples taken before the discharge from the hospital. The study of correlations revealed a positive correlation between the consumption of a full dose of proteins and the total increase in height (R=0.3, p<0.05), the increase in body weight (R=0.3, p<0.05). A negative correlation was found between the protein level and the duration of treatment in the hospital (R= -0.3, p<0.05). The level of free carnitine had a positive effect on the increase in body length (R=0.51, p<0.05), daily weight gain (R=0.3, p<0.05). A poor increase in body length was associated with a longer duration of respiratory support: the correlation had an inverse direction R= -0.4, p<0.05. Improving nutritional strategies has significant prospects for improving care development of full-term babies with critical perinatal states. Вивчали результати впливу підвищеного споживання протеїнів та L-карнітину в програмі харчування доношених новонароджених із захворюваннями перинатального періоду на результати фізичного розвитку та на показники лікування в стаціонарі. Метою роботи було вивчення кореляцій між короткотривалим більшим споживанням білка та карнітину доношеними новонародженими і результатами фізичного розвитку дітей, тривалістю госпітального виходжування. Досліджено показники життя 59 доношених дітей, у рандомізованому контрольованому дослідженні, у період з 2017 до 2020 року. Основним критичним захворюванням перинатального періоду в дітей обох груп виявлено гіпоксично-ішемічну енцефалопатію помірного ступеня – 86,7% та 86,2%, без статистично значущої різниці. Група (n=30) отримувала харчування молоком матері (CХ), друга група (n=29) отримувала аналогічне харчування з фортифікацією білковою добавкою (ГЗ) та дотацію L-карнітину протягом перебування в лікарні. На початку і в кінці лікування вивчали фізичний розвиток дітей та досліджували кореляційні зв’язки між отриманими даними. Немовлята обох груп не відрізнялися за характеристиками на початку дослідження. Пропорції ваги немовлят відповідали межам 50% перцентилю. Група підвищеного споживання білка та карнітину демонструвала кращі показники фізичного розвитку малюків, швидше відновлювала масу тіла. Маса тіла дітей групи ГЗ становила 3966,9±439,1 г порівняно з групою СХ 3554,6±452,3 г, при p=0,003. Показник збільшення довжини тіла в ГЗ вдвічі перевищував показник групи СХ. Споживання більшої дози білка супроводжувалось меншим часом перебування у відділенні інтенсивної терапії – 10,0 (8,0;12,0) днів проти 12,0 (11,0;16,0) днів, при U=235,0; p=0,002; раніше виписувались зі стаціонару – 21,0 (19,0; 27,0) день проти 26,5 (22,0; 31,0) днів, при U=267,0, p=0,01. Дотація карнітину в групі ГЗ приводила до підвищення рівня вільного карнітину в останніх зразках плазми крові перед випискою дітей додому. Дослідження кореляцій виявило позитивний кореляційний зв'язок між споживанням повної дози протеїнів та загальним збільшенням зросту (R=0,3, p<0,05), збільшенням маси тіла (R=0,3, p<0,05). Негативна кореляція виявлена між рівнем протеїну та тривалістю лікування в стаціонарі (R= -0,3, p<0,05). Рівень вільного карнітину позитивно впливав на збільшення довжини тіла – (R=0,51, p<0,05), щоденне збільшенням ваги (R=0,3, p<0,05). Погане збільшенням довжини тіла асоціювалася з більшою тривалістю респіраторної підтримки: кореляція мала зворотній напрямок R= -0,4, p<0,05. Удосконалення харчових стратегій має значні перспективи щодо покращення виходжування доношених дітей з критичними захворюваннями перинатального періоду.
Вплив споживання протеїну та карнітину на результати виходжування доношених новонароджених з критичними захворюваннями перинатального періоду
Keywords: hypoxic-ischemic encephalopathy; newborns; children; carnitin; physical development; breast milk; correlations; гіпоксично-ішемічна енцефалопатія; новонароджений; діти; карнітин; фізичний розвиток; грудне молоко; кореляційні зв'язки